Locating Europe: Recommendations and overview - Hansen, Kim Toft; Bengesser, Cathrin (2020)
Locating Europe through popular culture is not difficult. On international screens, Europe appears to be literally all over the place. European services attract international productions to ‘media meccas’ like Leavesden Studios in London, to overwhelming natural locations in Iceland, to ‘medieval’ nature in Northern Ireland or to strategically coordinated production services across the Czech Republic. Iceland appears in James Bond films, Berlin in American series like Homeland, Czech locations represent Poland in Danish drama, while international players on the market – like HBO and Netflix – increasingly film their productions on-location across the European continent. Today, locations have become ‘big business’ in film and television production. As a result, places are traded like never before, commercialized through screened popular culture and rebranded afterwards as tourist attractions. As much screened popular culture is adapted from printed media, literary place branding also plays an important part in reimagining European places. The relationship between popular culture and places is a powerful tool in catching the attention of media users, visitors and producers. Locating Europe through popular culture is not difficult. On international screens, Europe appears to be literally all over the place. European services attract international productions to ‘media meccas’ like Leavesden Studios in London, to overwhelming natural locations in Iceland, to ‘medieval’ nature in Northern Ireland or to strategically coordinated production services across the Czech Republic. Iceland appears in James Bond films, Berlin in American series like Homeland, Czech locations represent Poland in Danish drama, while international players on the market - like HBO and Netflix – increasingly film their productions on-location across the European continent. e European continent. Today, locations have become ‘big business’ in film and television production. As a result, places are traded like never before, commercialized through ...